2016
DOI: 10.1159/000447927
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Differentially Expressed Homer1 and Homer2 in Ischemic Stroke

Abstract: Background: Ischemic stroke (IS) is an extremely heterogeneous disease with variable pathogenesis. Due to the lack of early diagnostic marker, the mortality rate of IS remains high worldwide. The family of Homer plays an important role in the pathology of atherosclerotic plaque. In this study, we have investigated its expression pattern and clinical significance in IS. Methods: RT-qPCR was performed to detect the expression of Homer1, Homer2, and Homer3. Results: We found that the mRNA levels of Homer1 (p<0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…IS diagnosis is based primarily on imaging and neurological impairment. Unfortunately, current intervention and treatment of IS are still limited, including the following aspects: (1) Ischemic damage in brain tissue is not obvious within 24h after ischemic stroke by computed tomography (CT), and CT is mainly used to quickly eliminate intracranial tumors or cerebral hemorrhage 2 ) . (2) Magnetic resonance imaging (MRI) has higher sensitivity and specificity than CT, but most medical institutions in China cannot conduct MRI examinations 2 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IS diagnosis is based primarily on imaging and neurological impairment. Unfortunately, current intervention and treatment of IS are still limited, including the following aspects: (1) Ischemic damage in brain tissue is not obvious within 24h after ischemic stroke by computed tomography (CT), and CT is mainly used to quickly eliminate intracranial tumors or cerebral hemorrhage 2 ) . (2) Magnetic resonance imaging (MRI) has higher sensitivity and specificity than CT, but most medical institutions in China cannot conduct MRI examinations 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, current intervention and treatment of IS are still limited, including the following aspects: (1) Ischemic damage in brain tissue is not obvious within 24h after ischemic stroke by computed tomography (CT), and CT is mainly used to quickly eliminate intracranial tumors or cerebral hemorrhage 2 ) . (2) Magnetic resonance imaging (MRI) has higher sensitivity and specificity than CT, but most medical institutions in China cannot conduct MRI examinations 2 ) . (3) A recent systematic review suggested that the survival rate of IS patients who can receive thrombolytic therapy within 6h of symptom onset can be increased by 46.0%, and the disability rate caused by IS can be reduced by 42.1% 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…IS diagnosis is based primarily on imaging and neurological impairment. Unfortunately, current intervention and treatment of IS is still limited, including the following aspects: (1) Ischemic damage in brain tissue is not obvious within 24 hours after ischemic stroke by CT, and CT is mainly used to quickly eliminate intracranial tumors or cerebral hemorrhage [2]. (2) MRI has higher sensitivity and specificity than CT, but most medical institutions in China do not have the ability to conduct MRI examinations [2].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, current intervention and treatment of IS is still limited, including the following aspects: (1) Ischemic damage in brain tissue is not obvious within 24 hours after ischemic stroke by CT, and CT is mainly used to quickly eliminate intracranial tumors or cerebral hemorrhage [2]. (2) MRI has higher sensitivity and specificity than CT, but most medical institutions in China do not have the ability to conduct MRI examinations [2]. (3) A recent systematic review suggested that the survival rate of IS patients who can receive thrombolytic therapy within 6 hours of symptom onset can be increased by 46.0%, and the disability rate caused by IS can be reduced by 42.1% [3].…”
Section: Introductionmentioning
confidence: 99%